Tectonic controls on the spatial distribution and stratigraphic architecture of a net-transgressive shallow-marine syn-rift succession in a salt-influenced rift basin: Middle-to-Upper Jurassic, Norwegian Central North Sea - Mannie,AS; Jackson,CA-L; Hampson,GJ; Fraser,AJ (Journal of the Geological Society, 2016)
Syn-depositional deformation in salt-influenced rift basins is complex, being driven by a combination of normal faulting and the growth of salt structures such as diapirs. Due to a lack of data with which to simultaneously constrain basin structure and syn-rift stratigraphic architecture, we have a poor understanding of how these processes control shallow marine deposition in such settings. To improve our understanding we here use seismic reflection and borehole data from the Norwegian Central North Sea to investigate the role that syn-depositional fault growth and salt movement played in controlling the sub-regional stratigraphic architecture of a net-transgressive shallow-marine syn-rift succession (Middle-to-Late Jurassic). The rift-related structural framework, which is usually dominated by normal fault-bound horst and graben, is strongly modified where an Upper Permian salt layer (Zechstein Supergroup) is sufficiently thick and mobile to act as an intra-stratal detachment, giving rise to decoupled rift-related basement and cover structural styles. Furthermore, cover extension allows the salt to rise diapirically, resulting in the formation of large salt diapirs and supra-salt normal faults formed due to late-stage salt withdrawal and diapir collapse. Rift-related normal faulting and the growth of salt structures had a dual control on the depositional thickness and facies distribution within the net-transgressive, predominantly shallow-marine, Middle-to-Upper Jurassic syn-rift succession. The resulting facies architecture reflects a delicate balance between fault- and salt flow-driven accommodation creation and intra- and extra-basinal sediment supply. Where sediment supply and accumulation rate exceeded accommodation, little or no change in facies is observed across syn-depositional structures. In contrast, where accommodation outpaced sediment supply and accumulation rate, footwall-attached shorelines locally developed adjacent to large, thick-skinned normal f